Svobodni verz - Bjelčevič, Aleksander (Jezik in slovstvo, 1998)
Verse is a text with a double parsing: into words, syntagms, sentences, etc., and into specific intonation units. According to the latter principle, verse lines are equivalent in terms of a given property. In numerical verse, equivalence is established in terms of the number of syllables or stressed syllables, and in free verse in terms of the syntactic border at the end of the verse. There are three types of free verse: syntagmatic (borders of lines coincide with borders of syntagms), sentential (borders of lines coincide with those of sentences), and antisyntactic (there is a divergence of sentence and line borders).
Keywords: verzologija; verz; svobodni verz